Use of 3-Hydroxy-m-Toylol-1-o-Chlorophenyltriazene in the Spectrophotometric Determination of Copper(II) - Sharma, Kavita; Maroo, Usha; Maroo, Pradeep; Chauhan, R.S.; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
The title reagent has been used for spectrophotometric determination of Cu(II). The composition of yellow coloured complex has been found to be 1 : 2 (Cu : R) with absorption maximum at 390 nm in the pH range 6.6-7.2. Absorbance measurements were made at 400 nm. Beer's law was followed in the studied concentration range 2.0 x 10–5 M to 1.0 X 10–4 M. The value of molar absorptivity, Sandell's sensitivity, stability constant (log β) and free energy of formation were found to be 4107 L/mole cm, 15.47 ng/cm2, 10.10 and -13.77 kcal/mole respectively. Interference of twentyfive diverse ions has been examined.